(untitled) (gjstudies, 2020)
This research develops and validates an integrated framework combining COBIT(Control Objectives for Information and Related Technologies) for IT governanceand COSO (Committee of Sponsoring Organizations) for internal control to createfraud-resistant banking information systems. Through systematic analysis of 143banking institutions across North America and Europe from 2017 to 2019, this studydemonstrates that the integrated COBIT-COSO model significantly enhances auditreliability and fraud detection capabilities. The proposed framework addresses critical gaps in existing approaches by aligning IT governance objectives with internalcontrol activities through a unified risk assessment methodology. Empirical resultsindicate that banks implementing the integrated framework experienced 54% improvement in fraud detection rates and 63% reduction in false positives comparedto institutions using either framework in isolation. The research introduces a novelmaturity assessment tool that quantifies integration effectiveness and provides actionable guidance for implementation. Findings reveal that successful integrationrequires organizational commitment, cross-functional collaboration, and continuous monitoring mechanisms. This study contributes to both academic literatureand practical implementations by providing evidence-based insights for enhancingbanking information system resilience against evolving fraud threats.